SISTEM PENJUALAN BARANG PADA CV STAR DESIGN UNTUK BUSINESS TO BUSINESS BERBASIS WEB - Susanto, Susanto; Masithoh, Mauluddiah (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2024)
Sales Information System is an information system that provides information from  several  processes  which  include  procurement,  warehousing  and  reporting. Therefore, it is necessary to create an sales  Information System application to improve company performance processes which were originally manual to be computerized which will produce more detailed reports. Making this application is done by means of data collection, system planning, system analysis, system design and Database . Making application programs developed with PHP . The Database  used is MySQL and scripts are developed with Macromedia Dreamweaver. It can be  concluded  that  the  design  and  implementation  of  the  Sales   Information System  at  the  CV  Star  Design  is  ready  to  be  developed.  The  Inventory    on  this website uses the Business-to-Business. By logging into the website as a staff, the staff can fill in the required Inventory  data and can fill in the data on goods sold and  incoming  goods  from  suppliers,  all  of  which  will  later  be  entered  into  the Inventory    Database  .  If  all  data  has  been  processed,  there  will  be  an  Inventory  data menu where the data it contains the first entry date of the selected item to find out when the item entered so that when it is sold, the item sold is the oldest item. With the Business-to-Business method, the sales system will run sequentially thereby reducing the impact of damage from an item that is stored for too long in the storage of goods. In this web development using the Waterfall  method and implemented using php  and MySQL